2019
DOI: 10.2147/dddt.s229882
|View full text |Cite
|
Sign up to set email alerts
|

<p>Levonadifloxacin, a Novel Broad-Spectrum Anti-MRSA Benzoquinolizine Quinolone Agent: Review of Current Evidence</p>

Abstract: Levonadifloxacin and its prodrug alalevonadifloxacin are novel broad-spectrum anti-MRSA agents belonging to the benzoquinolizine subclass of quinolone, formulated for intravenous and oral administration, respectively. Various in vitro and in vivo studies have established their antimicrobial spectrum against clinically significant Gram-positive, Gram-negative, atypical, and anaerobic pathogens. The potent activity of levonadifloxacin against MRSA, quinolone-resistant Staphylococcus aureus, and hetero-vancomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 27 publications
0
61
0
Order By: Relevance
“…Quinolones and fluconazole are widely used antibacterial agents in treatment against infection clinically [37,38]. Credito et al has reported there was vitro synergy in combination of a new des-F(6)-quinolone DX-619 and vancomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Quinolones and fluconazole are widely used antibacterial agents in treatment against infection clinically [37,38]. Credito et al has reported there was vitro synergy in combination of a new des-F(6)-quinolone DX-619 and vancomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the levorotatory ( S )-isomer is approximately twice as active as the racemate against Gram-positive and Gram-negative pathogens [ 180 ]. This stereoisomer is under study as an arginine salt for intravenous administration (WCK 771) and is known as levonadifloxacin [ 193 ]. In general, the introduction of hydroxyl groups into the structure of a compound will produce analogues with increased hydrophilicity and low solubility in lipids.…”
Section: Compounds In Therapy Since 2000mentioning
confidence: 99%
“…Levonadifloxacin (WCK 771) ( S -(−)-9-fluoro-6,7-dihydro-8-(4-hydroxypiperidin-1-yl)-5-methyl-1-oxo-1H,5H-benzo[i,j] quinolizine-2-carboxylic acid L -arginine salt tetrahydrate) is administered parenterally (intravenous) in the form of an L -arginine salt while its prodrug alalevonadifloxacin (WCK 2349) (( S )-(−)-9-fluoro-8-(4- L -alaninyl oxypiperidin-1-yl)-5-methyl-6,7-dihydro-1-oxo-1H,5H-benzo[i,j] quinolizine-2-carboxylic acid, methane sulfonic acid salt) in the form developed of an L -alanine ester mesylate salt can be administered orally. Both substances are being developed by Wockhardt Limited (India) [ 193 , 196 ].…”
Section: Compounds In Therapy Since 2000mentioning
confidence: 99%
“…The well differentiated mechanism of action primarily towards the DNA gyrase has led to a distinctive potent activity of levonadifloxacin against MRSA, QRSA and hVISA strains. 38 Levonadifloxacin also retains a potent antibacterial activity against respiratory pathogens such as macrolideand penicillin -resistant S. pneumonia, S.pyogenes, H. influenza and M. catarhalis. It provides best in class epithelial lung fluid concentration, thereby promising potential in the treatment of lower respiratory tract infections.…”
Section: Need Of New Therapiesmentioning
confidence: 99%